Early Long-Term Memory Impairment and Changes in the Expression of Synaptic Plasticity-Associated Genes, in the McGill-R-Thy1-APP Rat Model of Alzheimer's-Like Brain Amyloidosis - Habif, Martín; Do Carmo, Sonia; Báez, María Verónica; Colettis, Natalia Claudia; Cercato, Magalí Cecilia; Salas, Daniela Alejandra; Acutain, María Florencia; Sister, Caterina Laura; Berkowicz, Valeria Laura; Canal, María Pilar; González Garello, Tomás; Cuello, A. Claudio; et al. (Frontiers in Aging Neuroscience, 2021)
Accruing evidence supports the hypothesis that memory deficits in early Alzheimer Disease (AD) might be due to synaptic failure caused by accumulation of intracellular amyloid beta (Aβ) oligomers, then secreted to the extracellular media. Transgenic mouse AD models provide valuable information on AD pathology. However, the failure to translate these findings to humans calls for models that better recapitulate the human pathology. McGill-R-Thy1-APP transgenic (Tg) rat expresses the human amyloid precursor protein (APP751) with the Swedish and Indiana mutations (of familial AD), leading to an AD-like slow-progressing brain amyloid pathology. Therefore, it offers a unique opportunity to investigate learning and memory abilities at early stages of AD, when Aβ accumulation is restricted to the intracellular compartment, prior to plaque deposition. Our goal was to further investigate early deficits in memory, particularly long-term memory in McGill-R-Thy1-APP heterozygous (Tg+/-) rats. Short-term- and long-term habituation to an open field were preserved in 3, 4 and 6-month-old (Tg+/-). However, long-term memory of inhibitory avoidance to a foot-shock, novel object-recognition and social approaching behavior were seriously impaired in 4 month old (Tg+/-) male rats, suggesting that they are unable to either consolidate and/or evoke such associative and discriminative memories with aversive, emotional and spatial components. The long-term memory deficits were accompanied by increased transcript levels of genes relevant to synaptic plasticity, learning and memory processing in the hippocampus, such as Grin2b, Dlg4, Camk2b and Syn1. Our findings indicate that in addition to the previously well-documented deficits in learning and memory, McGill-R-Thy1-APP rats display particular long-term-memory deficits and deep social behavior alterations at preplaque early stages of the pathology. This highlights the importance of Aβ oligomers and emphasizes the validity of the model to study AD-like early processes, with potentially predictive value.